Maximizing the profit of a HPP cascade considering hydraulic link via reservoirs - Mahnitko, A.Y.; Gerhards, J.H.; Lomane, T.V.; Varfolomejeva, R.V.; Oboskalov, V.P.; Koljasnikov, K.S. (Технічна електродинаміка, 2016)
At the conditions of market relationships and economic and financial independence of power companies, these are guided by the principle of achieving maximum efficiency in their actions. In the article is considered the problem formulation of HPP cascade operational mode determination, ensuring maximum profit from the sales of the generated electric power at the day-ahead market. Dynamic volumes of reservoirs are taken into account using the lag time between the waves of HPP water flow. The problem solution using the method of statistical modelling is approbated on the example of hypothetical cascade of three HPP. The results of the modelling of cascade operating regime are illustrated graphically. В условиях рыночных отношений, хозяйственной и финансовой самостоятельности энергетических предприятий, последние руководствуются принципом достижения максимума экономической эффективности от своей деятельности. В статье рассмотрена постановка задачи определения графика работы каскада ГЭС, обеспечивающего получение максимального дохода от продажи выработанной им электроэнергии на рынке «на сутки вперед». Динамические объемы водохранилищ учитываются с помощью времени добегания волны расходов воды между ГЭС. Решение задачи методом статистического моделирования апробировано на примере гипотетического каскада из трех ГЭС. Результаты моделирования режима работы рассматриваемого каскада ГЭС иллюстрируются графически. В умовах ринкових відносин, хазяйської та фінансової самостійності енергетичних підприємств останні керуються принципом досягнення максимуму економічної ефективності від своєї діяльності. У статті розглянуто постановку задачі визначення графіку роботи каскада ГЕС, що забезпечує одержання максимального доходу від продажу виробленої ним електроенергії на ринку «на добу вперед». Динамічні об'єми водосховищ враховуються за допомогою часу «добігання хвилі» витрат води між ГЕС. Розв'язування задачі методом статистичного моделювання апробовано на прикладі гіпотетичного каскаду з трьох ГЕС. Результати моделювання режиму роботи каскаду ГЕС, що розглядався, ілюстровано графічно.